Openness in evaluation - Pinto, Leonor Gaspar; Ochôa, Paula (Qualitative and Quantitative Methods in Libraries, 2019)
Evaluation is a vital part of every policy, programme, initiative or project framed by open movements. Sound evaluation strategies, procedures and criteria are needed to assess the impact of these movements on science, society and policy. Fostering access, collaboration and participation of groups that are in traditionally “peripheral” positions with respect to decision-making also means including them in evaluation processes, namely by employing participatory methods within libraries’ practices (e.g. ISO 16394, 2014). Using a meta-evaluative and transdisciplinary approach, this paper aims to discuss the concept of co-evaluation and how Research on Evaluation developed within Information Science can contribute to a research agenda and to enhance stakeholders and citizens’ involvement and competencies in open evaluation and open science.